2012
DOI: 10.19030/ajhs.v3i3.7134
|View full text |Cite
|
Sign up to set email alerts
|

Improving College Students' Success In Gateway Science Courses: Lessons Learned From An Anatomy And Physiology Workshop

Abstract: In this study, we evaluated the effectiveness of a two-week pre-anatomy and physiology workshop intended to contribute to student success in anatomy and physiology. The study showed that workshop participants had significantly higher post-test scores, better study habits, and generally felt more confident or prepared for anatomy and physiology. The workshop participants also reported that they understood membrane transport the least and organization of the body the most, information that may be useful in anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Selfassessments of confidence are frequently used in measurements of the effectiveness of transition programs (e.g. Abdullahi & Gannon, 2012;Boelen & Kenny 2009;Thalluri, 2016), as confidence is understood as a measure of selfefficacy, which has been widely linked to successful retention (Bandura, 1978;Lawrence, 2005). On a five-point Likert scale from 'not confident at all' to 'very confident', 43% of students selected the top two categories, which we interpret as a very favourable result.…”
Section: Resultsmentioning
confidence: 99%
“…Selfassessments of confidence are frequently used in measurements of the effectiveness of transition programs (e.g. Abdullahi & Gannon, 2012;Boelen & Kenny 2009;Thalluri, 2016), as confidence is understood as a measure of selfefficacy, which has been widely linked to successful retention (Bandura, 1978;Lawrence, 2005). On a five-point Likert scale from 'not confident at all' to 'very confident', 43% of students selected the top two categories, which we interpret as a very favourable result.…”
Section: Resultsmentioning
confidence: 99%
“…Students overwhelmingly stated in surveys that the quizzes helped them prepare for the course exams and master the course, with a high proportion of students also changing their study habits. This is a positive outcome as poor study habits is a major predictor of poor performance (McKee, 2002) and better preparation is correlated with success in the sciences (Abdullahi & Gannon, 2012;Harris et al, 2004;Hopper, 2011). It is encouraging to note that several students in the present study commented that they now felt more confident in self-monitoring their own performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hopper (2011) observed that, students enrolled in a one-hour supplement course meant to quickly identify at risk students, were more likely to achieve better grades and course completion rates. In a recent study, we showed that a two-week pre-Anatomy and Physiology workshop improves students' performance and attitudes to the course (Abdullahi & Gannon, 2012). In these studies, the improvements were attributed to a change in student skills and attitudes, although the possibility that high achievers were self selected couldn't be entirely ruled out.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sağlık bilimleri fakültesinde eğitim gören ebelik ve hemşirelik öğrencileri için anatomi dersi, daha sonraki yıllarda alacakları diğer derslerle bağlantılı olması açısından çok önemlidir. 3 Bu açıdan canlı vücudunun sağlığını koruma ve hasta insanı iyileştirme ve bakım verme görevini yürüten tüm sağlık çalışanları bu ders kapsamında insan vücudunu en iyi şekilde bilmek ve öğrenmek zorundadırlar. 4 Bu nedenle anatomi ve bu temel bilimin üzerine oturan geçerli ve gerekli bilgiler sayesinde sağlık profesyonelleri sağlam bir donanıma sahip olacakları düşünülmektedir.…”
Section: Introductionunclassified